Seen and unseen : visual culture of imperialism - Fotouhi, Sanaz; Zeiny, Esmaeil (Leiden : Brill, 2018)
'Seen and Unseen teases out and explores how visual mediums construct visual cultures that often create limited perspectives of certain issues and groups, specific to this volume, the representation of Islam and Muslims. It deals with fixed and stereotypical visual representations and explores alternative and challenging visual representations which reconstruct and dismantle existing belief systems. It approaches the topic from a vantage point of diverse multiple perspectives. Covering issues from Brunei, Iran, Egypt, and England and cyberspace, essays examine the visual cultures of how Islam and Muslim people are understood, misunderstood, misrepresented, or even embraced visually. Scholars in this volume draw on historical paintings, books and their covers, photography, and news to demonstrate the diversity and sometimes contradictory visual cultures that construct and adhere meaning to how Islam and Muslim people are seen. Contributors: Hoda Afshar, Jared Ahmed, Syed Farid Alatas, Sanaz Fotouhi, Christiane Gruber, Layla Hendow, Raihana M.M., Bruno Starrs and Esmaeil Zeiny'--
The arrest of Diponegoro: visual orientalism and its alternative / Syed Farid Alatas -- Images of the prophet Muhammad: brief thoughts on some European-Islamic encounters / Christiane Gruber -- Nightmarish visions? shifting visual representations of the'Islamic' terrorist throughout the'war on terror' / Jared Ahmad -- Oil and women: invisibility as power in Nawal El-Saadawi's love in the kingdom of oil / Layla Hendow --'World hijab day': positioning the hijabi in cyberspace / Raihanah M. M -- Contemporary Bruneian cinema in the context of Sharia law / D. Bruno Starrs -- Visual discourses of (un)veiling: revisiting women of Allah / Esmaeil Zeiny -- Visibility and veiling: Iranian art on the global scene / Hoda Afshar -- From woman to Tehran: the shifting representations of the Islamic Republic of Iran on book covers by Iranian writers in English / Sanaz Fotouhi.
Includes bibliographical references and index.
Keywords: Islam in art; Islam in mass media; Islam and culture -- Brunei; Islam and culture -- Egypt; Islam and culture -- England; Islam and culture -- Iran; Visual communication -- Brunei; Visual communication -- Egypt; Visual communication -- Iran